Phenotypic reversion of Aspergillus nidulans morphological deteriorated variants in the presence of osmotic stabilisers - S. M. G. Molina; J. L. Azevedo (Fungal Genetics Reports, 1994)
Strains of Aspergillus nidulans with chromosome duplications are unstable at mitosis. They produce sectors which are mainly of two types: improved sectors that result from partial or total loss of the duplication segment and deteriorated sectors having poor conidiation and dark brown mycelium. It is postulated that deteriorated variants carry additional duplications resulting from non-homologous sister-chromatid exchange within the duplicated segments. (Nga and Roper, 1968 Genetics 58: 193-209). Deteriorated sectors are unstable but can give more derivatives which probably are the result of transpositions of the tandem duplication segment to other regions of the genome (Azevedo and Roper, 1970 Genetical Research 16: 79-93). Crosses between these more stable deteriorated variants are not always successful due probably to incompatibility factors.